Pengaruh Brand Experience dan Brand Engagement terhadap Brand Loyalty dengan Brand Trust sebagai Variabel Mediasi - Sujana, Esa Riawati; Verinita; Sari, Dessy Kurnia (Jurnal Informatika Ekonomi Bisnis, 2023)
This study aims to look at the effect of brand experience and brand engagement mediated on brand loyalty mediated by brand trust in buttonscarves consumers in the city of Padang. The population is all consumers of buttonscarves products in the city of Padang. The sample criteria are respondents who have purchased buttonscarves products in the last 6 months and are domiciled in the city of Padang. The number of samples in the study was 130 respondents. The hypothesis test uses statistical analysis with one tailed. The results of the study show that brand engagement has an effect on brand loyalty and brand trust, brand trust has an effect on brand loyalty and brand engagement has an effect on brand loyalty through brand trust as mediation. Meanwhile, brand experience does not affect brand loyalty and brand trust directly and brand experience does not affect brand loyalty through mediation of brand trust.